2023
DOI: 10.1007/s10555-023-10134-x
|View full text |Cite
|
Sign up to set email alerts
|

Cell plasticity modulation by flavonoids in resistant breast carcinoma targeting the nuclear factor kappa B signaling

Peter Kubatka,
Lenka Koklesova,
Alena Mazurakova
et al.

Abstract: Cancer cell plasticity plays a crucial role in tumor initiation, progression, and metastasis and is implicated in the multiple cancer defense mechanisms associated with therapy resistance and therapy evasion. Cancer resistance represents one of the significant obstacles in the clinical management of cancer. Some reversal chemosensitizing agents have been developed to resolve this serious clinical problem, but they have not yet been proven applicable in oncological practice. Activated nuclear factor kappa B (NF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 205 publications
0
2
0
Order By: Relevance
“…XN has undergone extensive investigation as an anticancer agent, with studies reporting its ability to inhibit the proliferation of various cancers. These cancers include gastric cancer 32 , breast cancer 22 , lung cancer 21 , cholangiocarcinoma 33 and colon cancer 23 . Furthermore, our previous experiments revealed that XN impeded cell proliferation by inducing paraptosis in leukemia cells 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…XN has undergone extensive investigation as an anticancer agent, with studies reporting its ability to inhibit the proliferation of various cancers. These cancers include gastric cancer 32 , breast cancer 22 , lung cancer 21 , cholangiocarcinoma 33 and colon cancer 23 . Furthermore, our previous experiments revealed that XN impeded cell proliferation by inducing paraptosis in leukemia cells 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Xanthohumol (XN), a pentenyl avonoid extracted from hops, possesses anticancer, antioxidant, antibacterial, and anti-in ammatory activities 20 . Research has demonstrated that XN can impede the growth of various cancer types, such as lung cancer 21 , breast cancer 22 , colon cancer 23 , prostate cancer 24 , liver cancer 25 , and other cancers. This inhibition effect could be achieved by suppressing tumor cell proliferation, invasion, and migration, causing cell cycle arrest and inducing apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other study data provide evidence that the phytopharmaceutical stimulates autophagy in cancer cells through Beclin-1-independent pathways, including the modulation of Wnt/β-catenin signaling and direct inhibition of the mTOR-Unc-51-like kinase 1 pathway via ATP competition, indicating its multitarget mode of action and the importance of autophagy [ 56 , 169 ] ( Figure 7 ). Additionally, the mechanism of enhanced exocytosis was shown to be associated with resistance to therapy in conjunction with up-regulated NF-κB signaling, leading to the overexpression of chemoresistance proteins such as multidrug resistance protein (MDR1) and multidrug resistance-linked protein 1 (MRP1) in BC [ 170 ]. In this regard, resveratrol has been demonstrated to act as a chemosensitizer by modulating the expression of MDR1 and MRP1 in multidrug-resistant BC cells [ 171 ].…”
Section: Resveratrolmentioning
confidence: 99%
“…Orientin, a member of the apigenin-8- C -glucoside family, is a flavonoid widespread in various edible plants. It is a biologically active compound with multiple properties, making it the focus of interest in numerous studies. Orientin inhibits oxidative stress-induced endoplasmic reticulum stress and mitochondrial dysfunction via the AMPK pathway. However, the potential of orientin to facilitate skeletal-muscle-fiber-type transformation remains unexplored.…”
Section: Introductionmentioning
confidence: 99%